O-037 Comparative safety and efficacy of combined intravenous thrombolysis and mechanical thrombectomy with mechanical thrombectomy alone in emergent large vessel occlusion. (23rd July 2017) - Goyal, N; Tsivgoulis, G; Frei, D; Turk, A; Baxter, B; Froehler, M; Mocco, J; Ishfaq, M; Hoit, D; Elijovich, L; Loy, D; Turner, R; et al.
Abstract : Background: Mechanical thrombectomy (MT) for acute ischemic stroke (AIS) patients with emergent large-vessel occlusions (ELVO) has become the standard of care. Current top-tier guidelines recommend intravenous thrombolysis (IVT) administration for ELVO patients before MT if presented within recommended time window for IVT. However, it is not known whether IVT is of added benefit in patients undergoing MT. In this multicenter study we sought to evaluate if there are any differences in safety and efficacy outcomes in ELVO patients treated with combined IVT and MT versus MT alone. Methods: We conducted an observational study on consecutive AIS patients with ELVO who underwent MT at 6 high-volume endovascular centers. Standard safety and efficacy outcomes were compared between patients who underwent combined IVT and MT vs. MT alone. In addition, we performed propensity-matched analyses (PSM) to compare safety and efficacy outcomes in both groups. Successful recanalization was defined as a Thrombolysis in Cerebral Infarction (TICI) score of 2b/3. Symptomatic intracranial hemorrhage (sICH) was defined as presence of a parenchymal hematoma type 2 on brain computed tomography and/or magnetic resonance imagining accounting for deterioration with an increase in NIHSS-score of ≥4 points within 36 hours from treatment. Functional independence (FI) was defined as modified Rankin Stroke (mRS) scale of 0–2 at 3 months. Favorable functional outcome (FFO) was defined as mRS of 0–1 at 3 months and functional improvement was defined as mRS shift by 1-point decrease in mRS-score. Results: A total of 292 patients (51%) underwent IVT and MT (mean age 62±17, median NIHSS: 17 (IQR 13–21)], while 277 patients (49%) underwent MT monotherapy, [mean age 61±20, median NIHSS 16 (IQR: 12–21)]. The combined therapy group tended to have higher rates of FI (41% vs. 34%, p=0.079) and greater functional improvement (p=0.037) at three months. After PSM, 208 patients in the combined therapy group [mean age 63±17, median NIHSS: 17 (IQR 13–21)], and 104 patients [mean age 62±20, median NIHSS: 16 (IQR 13–21)] in MT monotherapy group were matched. The combined therapy group did not differ significantly in terms of rates of successful recanalization (81% vs 77%, p=0.443) and rates of sICH (7% vs 11%, p=0.202) compared to MT monotherapy group. The combined therapy group tended to have higher rates of FI (48% vs. 37%, p=0.063), greater functional improvement (p=0.022) and lower rates of mortality (18% vs 29%, p=0.028) at three months. IVT pre-treatment was independently (p<0.05) associated with higher odds of FI or functional improvement and lower likelihood of mortality at three-months on multivariable logistic regression analyses in the matched subgroups of patients. Conclusions: Our multicenter study appears to provide observational evidence that IVT pretreatment may improve MT outcomes in ELVO patients. The comparative efficacy of MT+IVT vs. MT monotherapy can be established only in the settings of a randomized-controlled clinical trial. Disclosures: N. Goyal: None. G. Tsivgoulis: None. D. Frei: None. A. Turk: None. B. Baxter: None. M. Froehler: None. J. Mocco: None. M. Ishfaq: None. D. Hoit: None. L. Elijovich: None. D. Loy: None. R. Turner: None. J. Mascitelli: None. K. Espaillat: None. A. Alexandrov: None. A. Alexandrov: None. A. Arthur: None.